PENGARUH SOLVABILITAS DAN PROFITABILITAS TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR (Studi Pada Subsektor Pulp dan Paper Yang Terdaftar di BEI Periode 2017-2020) - Lidya Agustin; Siti Rosyafah; Tri Lestari (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2021)
Financial performance is the result achieved by the company's management to find out in managing company assets effectively during a certain period. An uncertain economy causes a high risk of a company experiencing poor financial performance or bankruptcy, to determine whether a company's financial performance is good or not, it can be seen from the company's ability to pay off its debts through solvency and profitability. The purpose of this study was to determine the effect of solvency and profitability on the company's financial performance. This study uses a quantitative approach with data collection using purposive sampling method. The population of this study are pulp and paper manufacturing companies listed on the Indonesian stock exchange with 8 out of a total of 10 companies. The analytical method used is multiple linear regression analysis with hypothesis testing, namely t test, F test and R² test. The results showed that partially solvency (debt to total asset ratio and debt to equity ratio) had no significant effect on financial performance, and profitability (return on equity and net profit margin) partially had a significant effect on financial performance. Simultaneously solvency (debt to total asset ratio and debt to equity ratio) and profitability (return on assets and net profit margin) have a significant effect on financial performance. Meanwhile, the dominant influence is profitability (net profit margin).